SCHOOL READINESS AND SCHOOL SUCCESS - Yadav, Padma (THE PRIMARY TEACHER, 2011)
The study highlights the relationship between school readiness and school success. Factors influencing school readiness and school success have also been analysed. School success here means academic achievement/attainment of children in Class I. The study was both exploratory and descriptive in nature. The sample of the study consisted of14 schools. Total 505 children of Class I and their performance using teacher made tests were observed throughout the year. Interaction was made with Heads of the selected school, Class I teachers and parents. Focus group discussions were held with children of Class I to gauge the factors influencing school success. It was found that parental education and parental income had emerged as important factors. Children with pre-school experience showed better performance. Experiences of ECE attained through various models of pre-schooling were found significant in predicting school success. Achievement in reading and numeracy was relatively lower in children up to 5½ years than those of above 6 years. Male children performed better than female children on reading and numeracy. Female children performed better on developmental activities.